CXCL-8-dependent and -independent neutrophil activation in COPD: experiences from a pilot study of the CXCR2 antagonist danirixin. Issue 4 (10th November 2020) - Keir, Holly R.; Richardson, Hollian; Fillmore, Christina; Shoemark, Amelia; Lazaar, Aili L.; Miller, Bruce E.; Tal-Singer, Ruth; Chalmers, James D.; Mohan, Divya
Neutrophils are central to the pathophysiology of COPD, yet there are no licensed therapies directly targeting neutrophil-mediated inflammation [1]. Neutrophils are recruited to the COPD airway via chemoattractants such as interleukin-8 (CXCL-8) and are activated by pro-inflammatory cytokines abundant in inflamed airways [2]. Following activation, neutrophils can degranulate, releasing damaging proteases and mediators, or can form neutrophil extracellular traps (NETs), which consist of neutrophil DNA, granule products and antimicrobial proteins that trap microbes and prevent bacterial dissemination [3]. However, excessive NET formation (or NETosis) may cause host damage and has been implicated in multiple diseases [4–6], including COPD [4, 7–9]. The implications of these findings are significant for development of CXCR2 antagonists and other mechanisms targeting neutrophil activation or NETosis, suggesting that IL-8-dependent mechanisms will only work in a subset of COPD patients https://bit.ly/32SeisO